How Does Developing Green Agriculture Affect Poverty? Evidence from China’s Prefecture-Level Cities - Xingling Jiang; Yong Sun; Mou Shen; Lixia Tang (Agriculture, 2024)
Eradicating poverty and improving human well-being are pivotal objectives for achieving global sustainable development. Sustainable agriculture, as a key domain, plays a crucial role in addressing poverty. However, to date, there remains insufficient research on the specific impact of agricultural green development on poverty. To bridge this gap, we utilize panel data from 273 prefecture-level cities in China from 2006 to 2022 to explore how agricultural green development affects poverty based on constructing a regional multidimensional poverty index and an index of green agriculture. Our study reveals that agricultural green development effectively reduces poverty, particularly in regions of deep poverty and the eastern part of China. Further mediating analysis indicates the alleviation of poverty by agricultural green development through the infrastructure, the industrial structure, and the green technology innovation effect. Our findings offer valuable insights for informing policies on agricultural green development and poverty reduction, as well as for improving government resource allocation and strengthening resilience in impoverished areas. By deepening our understanding of the link between green agriculture and poverty, this research significantly contributes to global agricultural sustainability and expedites poverty eradication worldwide.